The Impact of the Implementation of the Regional Financial Information System (SIPKD) on the Effectiveness of Regional Financial Management - Abdul Robi padri (Sekolah Tinggi Agama Islam Kuningan, 2025)
This study analyzes the impact of the Regional Financial Information System (SIPKD) implementation on the effectiveness of regional financial management in Indonesia. As a technology-based platform, SIPKD is expected to enhance efficiency, transparency, and accountability in public financial governance-yet empirical evidence on its direct contribution remains limited. This research is one of the few quantitative studies that examines SIPKD's impact across multiple regional governments using measurable performance indicators. The study employs an explanatory research design with a purposive sample of 100 regional governments. Data were collected through documentation and questionnaires, then analyzed using simple linear regression. Findings reveal that SIPKD implementation has a positive and significant effect on regional financial management effectiveness, with a regression coefficient of 0.72 (p < 0.001). Regions with higher levels of implementation show improved budget absorption, more accurate financial reporting, and a greater likelihood of obtaining an Unqualified Audit Opinion (WTP) from the Supreme Audit Agency (BPK). These results reinforce the theory that robust information systems can substantially enhance public sector performance. Theoretically, this study expands the understanding of digital governance systems in the public sector. Practically, it suggests that central and regional governments should strengthen SIPKD implementation through human resource capacity building, adequate infrastructure provision, and sustainable system integration to achieve optimal governance outcomes.